Pinoy Solutions to Corruption - Briones, Leonor Magtolis; Reyes, Danilo R.; Domingo, Ma. Oliva Z. ([Manila] USAID-Management Systems International and Coffey International Development, 2011)
This document discusses the need for Filipino solutions to corruption in the Philippines. It notes that corruption has been a problem since Spanish colonial times and is now deeply ingrained in society and governance. While many studies have been done on corruption and reforms have been implemented, the problem persists. It discusses a seminal 1975 study by the University of the Philippines that took a comprehensive, multidisciplinary approach to understanding corruption. The study examined the historical, sociological, cultural and administrative dimensions of corruption. It concluded that only Filipinos can develop effective solutions to corruption given their understanding of these complex, contextual factors.
Chapter 1 Why the Filipino Solutions to Graft and Corruption? / Prof. Leonor Magtolis Briones (Ret.) -- Chapter 2 Gararap and Corarap Pinoy Style/ Prof. Leonor Magtolis Briones (Ret.) -- Chapter 3 Chronicling Corruption in the Philippines: A Brief Historical Background Up to 2004/ Prof. Danilo R. Reyes -- Chapter 4 Chronicling Corruption in the Philippines, 2005–May 2011: The Road to Perdition..? / Prof. Ma. Oliva Z. Domingo -- Chapter 5 Learning from Pinoy Successes/ Prof. Leonor Magtolis Briones (Ret.) -- Chapter 6 Framework for a National Anti-Corruption Program/ Prof. Leonor Magtolis Briones (Ret.) -- Chapter 7 From Pinoys to P’noy: Specific Solutions to Corruption/ Prof. Leonor Magtolis Briones (Ret.).
Keywords: Political corruption -- Philippines -- Prevention; Public institutions -- Corrupt practices -- Philippines; Corruption investigation -- Philippines